2018
DOI: 10.5334/tohm.436
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia 27: A Review and Characterization of an Evolving Phenotype

Abstract: Background: Spinocerebellar ataxia (SCA) is an uncommon form of progressive cerebellar ataxia with multiple genetic causes and marked variability in phenotypic expression even across patients with identical genetic abnormalities. SCA27 is a recently identified SCA caused by mutations in the Fibroblast Growth Factor 14 gene, with a phenotypic expression that is only beginning to be fully appreciated. We report here a case of a 70-year-old male who presented with slowly worsening tremor and gait instability that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Other symptoms, including orofacial dyskinesias, psychiatric manifestations, cognitive delay, or parkinsonism are common. Symptom onset occurs early in life nevertheless the disease course is usually very slow and motor function is maintained through life in most of the patients 1 . More recently, animal model studies and genome‐wide association studies suggested that FGF14 may be a risk factor for various neuropsychiatric diseases including depression addiction and schizophrenia, as well as neurodegenerative diseases, 2,3 FGF14 encodes fibroblast growth factor 14 highly expressed in the brain and especially in Purkinje cells, where it interacts with voltage‐gated Na+ channels to regulate neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms, including orofacial dyskinesias, psychiatric manifestations, cognitive delay, or parkinsonism are common. Symptom onset occurs early in life nevertheless the disease course is usually very slow and motor function is maintained through life in most of the patients 1 . More recently, animal model studies and genome‐wide association studies suggested that FGF14 may be a risk factor for various neuropsychiatric diseases including depression addiction and schizophrenia, as well as neurodegenerative diseases, 2,3 FGF14 encodes fibroblast growth factor 14 highly expressed in the brain and especially in Purkinje cells, where it interacts with voltage‐gated Na+ channels to regulate neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Originally identified as the genetic locus of missense mutations leading to spinocerebellar ataxia type 27 [1][2][3][4][5][6][7], FGF14 is an emerging risk factor for neuropsychiatric disorders [8]. Unlike canonical secreted FGFs, which act through activation of FGF receptor signaling, FGF14 is retained intracellularly where it has been shown to regulate ion channel function [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The common association of FGF14 with DBN and SCA27 poses a key question: what is the phenotypic similarity between isolated DBN and those with spinocerebellar ataxia type 27? The latter, a typical childhood onset disorder, presents with tremor, robust gait ataxia, depression, and anger outbursts [10][11][12][13][14]. Nystagmus is reported in about 84% of spinocerebellar ataxia patients, but DBN is extremely rare and was reported only twice in the literature [12].…”
mentioning
confidence: 99%
“…The latter, a typical childhood onset disorder, presents with tremor, robust gait ataxia, depression, and anger outbursts [10][11][12][13][14]. Nystagmus is reported in about 84% of spinocerebellar ataxia patients, but DBN is extremely rare and was reported only twice in the literature [12]. Parkinsonism is another feature of spinocerebellar ataxia type 27 [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation